Wideband coupled-line BPF with high-selectivity based on parallel transmission line signal interference technique for cellular base stations applications - Firmli, Maroua; Zatni, Abdelkarim (Bulletin of Electrical Engineering and Informatics, 2024)
This paper presents a novel approach involving a modified wideband parallel coupled line bandpass filter (BPF). The proposed modification aims to achieve both enhanced skirt selectivity and simplified configuration, while ensuring the prevention from discontinuities between adjacent segments. The improvements in the performance of the filter’s structure are achieved through the integration of a signal-interference filtering model using parallel transmission line with distinct impedance values and electrical lengths at the input/output of the filter. This integration gives rise to the generation of multiple transmission zeros (TZs), thereby bolstering attenuation within both in-band and out-of-band frequency ranges. For the purpose of concept validation, a 3?? wideband band-pass filter with ?0=2.45 Ghz, accompanied by a fractional bandwidth of 50% was designed and simulated using microstrip RO6010 substrate. The outcomes of the simulation exhibit good performance, characterized by minimal insertion loss, wide bandwidth and the presence of seven TZs within the passband, resulting in high selectivity and sharp stopband rejection level.